THE FOURTH SEMESTER STUDENTS’ PERCEPTION ON DIFFICULTIES IN LISTENING FOR MINI TALK AT ENGLISH EDUCATION STUDY PROGRAM OF BENGKULU UNIVERSITY - Fitra Florensia; Kasmaini Kasmaini; Sufiyandi Sufiyandi (Universitas Bengkulu, 2021)
This research aimed to find out the perception on difficulties faced by the fourth semester students of English Education in listening for mini talk and the strategies used by the students of English Education to succeed in listening for mini talk. The respondents of this research were 70 students of fourth semester of English education study program Bengkulu University in academic year 2021/2022. This research used descriptive quantitative method. The gathering of the data by using questionnaire and interview. The questionnaire adopted from Hamouda (2013). The result of this study showed that the difficulties in listening for mini talk such as: physical setting, listening material, lack of concentration, speaker, listener, psychological characteristics and linguistic aspects. While the way to overcome the difficulties in listening for mini talk were practice listening to familiar topics, knowing the topic of listening, watching speech frequently, practicing English with friends.